Mechanical and Membrane Keyboard Typing Assessment Using Surface Electromyography (sEMG). (September 2015) - Pham, Tri; Kelling, Nicholas
There are many different types of keyboards available for use. However, the mechanical keyboard is becoming more popular with enthusiast computer users. Vendors and users alike proclaim that they provide increased typing speeds and that less physical effort is required to activate the keyswitches due to the additional tactile and auditory feedback from the keyswitch design. This study investigates words per minute (WPM), error percentage, and surface electromyography (EMG) of the flexor arm muscle activity during a typing task using a membrane and mechanical keyboard. Results showed statistical significance with both flexor muscles exerting less effort on a mechanical keyboard. Advantages were not limited the mechanical keyboard with WPM revealing greater typing speeds with the standard membrane keyboard.